2021
DOI: 10.1002/jbt.22716
|View full text |Cite
|
Sign up to set email alerts
|

Proanthocyanidin alleviates doxorubicin‐induced cardiac injury by inhibiting NF‐kB pathway and modulating oxidative stress, cell cycle, and fibrogenesis

Abstract: This study investigated the potential mechanism(s) and the signaling pathway(s) underlying the prophylactic effect of proanthocyanidin extract (PE) against doxorubicin (DOX)‐induced cardiotoxicity in rats. A total of 32 male albino rats were randomly allocated into four groups. Control rats were orally administrated normal saline. Rats in the second group were orally administrated PE (50 mg/kg bw/once daily) for 4 weeks. Rats in the third group were intraperitoneally injected with DOX (10 mg/kg on Days 3, 9, 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 80 publications
(97 reference statements)
0
12
0
Order By: Relevance
“…In the report of nishimura's, following repeated administration of isoprenaline in rats (0.5 mg/kg), the relative expression of miR-208a in plasma increases significantly after 2 days and decreases after 4 days ( 29 ). Sadek et al ( 57 ) showed that fibrogenic factors, such as α smooth muscle actin, TGF-β1 and p16 INK4A , are upregulated following DOX-induced cardiac injury. TGF-β1 binds to type II TGF-β receptor, subsequently activating type I TGF-β receptor.…”
Section: Discussionmentioning
confidence: 99%
“…In the report of nishimura's, following repeated administration of isoprenaline in rats (0.5 mg/kg), the relative expression of miR-208a in plasma increases significantly after 2 days and decreases after 4 days ( 29 ). Sadek et al ( 57 ) showed that fibrogenic factors, such as α smooth muscle actin, TGF-β1 and p16 INK4A , are upregulated following DOX-induced cardiac injury. TGF-β1 binds to type II TGF-β receptor, subsequently activating type I TGF-β receptor.…”
Section: Discussionmentioning
confidence: 99%
“…Protection of the heart by strengthening the cardiac antioxidant defense system against DOX-induced cardiac injury caused by ROS formation plays an important role in protection against DOX-induced myocardial damage (Arafa et al 2014, Oner et al 2019. Previous studies reported that DOX application caused impairment in antioxidant defense such as SOD, CAT and GSH (Qi et al 2020, Sadek et al 2021. As antioxidant enzymes, SOD and CAT scavenge superoxide anion and hydrogen peroxide.…”
Section: Discussionmentioning
confidence: 99%
“…TGF‐β/ALK5/Smad signaling plays opposite roles in cancer progression (Connolly et al, 2011; Gu & Feng, 2018; M. Zhang et al, 2011). Acting as a tumor suppressor, TGF‐β/ALK5/Smad signaling inhibits proliferation and enhances differentiation by activating cyclin‐dependent kinase inhibitors, such as p16INK4a, p21cip1, and p27Kip1, and downregulating transcription factors, such as Myc, Id1, and Id2, in normal epithelial cells and premalignant lesion cells (S. H. Choi, Barker, Gerber, Letterio, & Kim, 2020; Sadek, Mahmoud, Zeweil, & Abouzed, 2021; Visram, Dasari, Anderson, Kumar, & Kourelis, 2021). In contrast, when malignant tumor reaches an advanced stage, TGF‐β/ALK5/Smad promotes tumor progression prominently by inducing EMT, reinforcing tumor–stroma interaction, and leading to escaping immune system surveillance.…”
Section: Discussionmentioning
confidence: 99%